Pulsation in Intermediate-Mass Stars - Balona, Luis A. (Frontiers in Astronomy and Space Sciences, 2018)
A new perspective of pulsation in stars within the δ Scuti instability strip has recently emerged as a result of Kepler observations. The majority of stars within the instability strip do not pulsate and practically all δ Scuti stars contain low frequencies. Because γ Doradus stars co-exist with δ Sct stars in the same region of the instability strip, it follows that γ Dor stars are driven by the same mechanism as δ Sct stars. The difference must be due to different mode selection processes. The search for an unknown damping factor which is missing from the models will be essential for further progress. Maia variables and hot γ Dor stars are briefly discussed. Luminosities of roAp stars obtained from Gaia DR2 parallaxes and spectroscopic effective temperatures show that the roAp stars are slightly evolved with temperatures in the range 6,300–8,300 K, considerably cooler than predicted by the models. The roAp stars and stars with solar-like oscillations share the same mass—temperature—luminosity relation, but with frequencies which are about 50 percent higher. This suggests that roAp frequencies are determined by the critical acoustic frequency, but this frequency is larger than in standard models, perhaps as a result of a temperature inversion in the atmosphere.